DAUR OPTIMAL TEGAKAN GMELINA PADA DUA PROYEK KARBON: MEMPERPANJANG DAUR DAN AFORESTASI - Yonky Indrajaya; Satria Astana (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Forest plantation may contribute economically and socially as a provider of wood raw materials for industry and providing jobs for local people. In addition, forest plantation may also contribute as watershed protection and carbon sequestration. Projects on carbon sequestration from plantation forest can be conducted in two types: (1) afforestation and (2) lengthening forest rotation. One of the potential carbon markets operationalized in the field is voluntary market with Verified Carbon Standard mechanism. This study aimed to analyze the optimal rotations of gmelina forests on two carbon projects: lengthening rotation and afforestation. The method used in this study was by using Hartman model ( i.e. Faustmann) by maximizing profit with the revenue source from timber and carbon sequestrationproject. The results of this study showed that carbon price will affect the optimal rotation for lengthening forest rotation of VCS project. Meanwhile, for VCS afforestation project, carbon price had no effect on the optimal rotation on gmelina forest. The NPV value of afforestation project was relatively higher than that of NPV value of lengthening forest rotation project, since the amount of carbon that can be credited relatively higher in afforestation project.